Polityczna i pedagogiczna aktywność Janusza Jędrzejewicza na emigracji (1939–1951) - Stelmasiak, Izabela (Biuletyn Historii Wychowania, 2009)
The exile years of Janusz Jędrzejewicz (1939-1951), a prominent and reputed educator of the inter-war Poland, deserve much of our attention. After the outbreak of the war, Jędrzejewicz initially took some effort to return to active military duty but these attempts failed to be successful. Along with the evacuation of the government, the Jędrzejewiczs had to leave Poland for Romania and had to remain there as exiles. Dull, everyday routine in exile in Romania was interspersed with Jędrzejewicz’s involvement in teaching maths and in meetings with fellow exiles, the followers of Józef Piłsudzki. The years from July 1940 until the end of the year, Jędrzejewicz and his family spent in Turkey. In the dire straits he was in at the time, to minimize stress and inconvenience in housing, he managed to find some balance and relief in his political and social activity. Jędrzejewicz managed to establish contacts with other exiles, notably Tatar, Caucasian and Ukrainian exiles. As a result of the meetings with the non-Polish émigrés, the concept of the so-called “Międzymorze – Intermarum”, a proposed federation of countries stretching from the Baltic Sea to the Black Sea, emerged. The years between 1940 and 1942 Jędzerzejowicz and his family spent in Tel-Aviv in Palestine. The local Polish political and military circles were closely associated with former “colonels” and Gen. Sławoj-Składkowski’s supporters and were labelled as “steadfast” or “unyielding”. In a straightforward way, the leadership of this group fell to Jędrzejewicz as the one who was the highest ranking Pilsudski-ite among them. The group became the core of the political movement founded upon a concept that underlined the ideas of the late marshal and represented their supporters in the Near East. Jędrzejewicz was very active in writing articles on social and political subjects and in giving lectures, including notably the one delivered on March 19, 1941 and entitled “On the occasion of the anniversary of the name day of First Marshal of Poland” He was also involved in talks with leaders of local Jewish and Arabic population. The presented concept of “Intermarum” was received with interest by politicians in exile from the Baltics, Slovakia, the Czech Republic and Hungary. It also formed an alternative to the realpolitik exercised by the government in exile. An important initiative of the group of the Pilsudski-ites was to publish Biuletyn Informacyjny (News Bulletin), and then to transform it into the official monthly Na Straży (On guard). The editor-in-chief of the periodical was Jędrzejewicz himself (from issue 18th onwards). In the course of time, still in Tel-Aviv and Jerusalem, the Piłsudski-ite groups grew more and more members. These circles, physically far from the government in exile in London and its influence, were thus more independent and formed a sort of a mutation and an alternative to the London-based Związek Pracy Państwowej (State Labour Union). Under the leadership of Janusz Jędrzejewicz, the Piłsudzki-ites in Palestine organized themselves in Związek Pracy dla Państwa (Union of Work for the State). The Polish political scene in exile was going through many dramatic changes and transformations. Political tension was aggravated further by Prof. Kot’s action who had returned from the Soviet Union in mid-1942. He perceived the activity of some of Polish exiles in the Near East as politically detrimental and anti-government. As for Prof Kot’s intense dislike for Jędrzejewicz, it was guided by the two following reasons: the latter’s influence in circles overtly reluctant to accept the stance adopted by the government represented by Gen. Sikorski, and, secondly, his personal grudge and resentment towards the former minister of religious affairs and education (Polish: MriOP). The political situation of the years 1944-1946 was decisive in creating the atmosphere less negative and more cooperative, and ultimately led to the emergence of the idea of a common platform for reconciliation and understanding for all splinter groups of Piłsudski followers. The common denominator for all was to be the Independence League, a political party in exile, of which, until 1947, Jędrzejewicz knew very little about. From 1942 the Jędrzejewiczs lived in Jerusalem, where they enjoyed good rapport and relations with local Arab leaders. Despite some health problems, Jędrzejewicz engaged himself in a series of lectures and continued to edit the periodical Na Straży. Soon, however, he was forced to step down this post due to aggravating health problems. Towards the end of 1946, the former prime minister was transferred to the reserve. This helped Jędrzejewicz to obtain a decision to be moved to Great Britain. Before he left Jerusalem, however, he spent half a year with his family in harsh conditions of El Kantara field hospital, which was also a transit camp for war refugees. The circles of the London-based Pilsudski-ites were very much counting on Jędrzejewicz’s Związek Pracy dla Państwa. The promoters of the Independence League also viewed the former prime minister, who was a one-time trustworthy aide to Marshal Piłsudski, as their potential leader. Jędrzejewicz himself was quite aware of his assets and the position he enjoyed within the hierarchy of values as a Piłsudski-ite and, despite bad health, was ready to support the League. In the first half of 1948, with the help of Jędrzejewicz, the fundamentals of the political program of the Poland’s Independence League were established. However, the following infightings and quarrels as to who was to head the League made Jędrzejewicz step down from the position of the leader of the League. From that time on, his activity was limited to writing articles and the participation in the work for the board of trustees of the London Piłsudski Institute. Jędrzejewicz’s last years of his life were undoubtedly influenced by his poor health (1948-1951). He was repeatedly hospitalized, which was taken advantage of by his political opponents in 1948. His physical state was very much influenced by his mental condition, which was a result the victimization and persecution he experienced between 1939-1943. An emotional shock for him was undoubtedly the news about his son who had been shot by the Germans in 1943, and the death of his former wife, Maria Stattler, in 1944. Eventually, all his energy was directed at administrative and research work. With his participation, or at his initiative, four research institutes were established at the time. The intention was to conduct historical or political science research there. Janusz Jędrzejewicz died on March 16th 1951. In exile, he was unfortunate enough to experience ostracism from fellow Poles, both as a politician and as a man. Still, he was far from shunning the world and, with dignity, he carried out his mission of executing the tasks once set by his Commander. As an exile, he was just as well a good representative of a Piłsudski-ite with a characteristic appropriate system of values that determined his life style. The ongoing internalization of the imponderables of his beloved Commander was though respected in the multi-faceted realities of Polish exile life.